2019
DOI: 10.1007/s00520-019-05058-8
|View full text |Cite
|
Sign up to set email alerts
|

Development of an evidence-based decision aid on complementary and alternative medicine (CAM) and pain for parents of children with cancer

Abstract: Purpose To develop an evidence-based decision aid for parents of children with cancer and to help guide them in the use of complementary and alternative medicine (CAM) for cancer care. Methods This study had a mixed research design. The needs of parents were investigated by survey and focus group. A systematic review and meta-analysis were performed on the effectiveness of CAM using Grading of Recommendations Assessment, Development and Evaluation (GRADE). Clinical experts were interviewed and a decision aid o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
10
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 35 publications
(46 reference statements)
0
10
0
2
Order By: Relevance
“…Other nonpharmaceutical interventions such as music therapy (Jong et al, 2020) and acupressure (Psihogios et al, 2019) have also gradually shown increasing use with few side effects. Animal-assisted intervention (AAI), also called pet therapy, acts as a psychosocial and adjunctive treatment for symptom control (Levinson, 1965).…”
Section: Introductionmentioning
confidence: 99%
“…Other nonpharmaceutical interventions such as music therapy (Jong et al, 2020) and acupressure (Psihogios et al, 2019) have also gradually shown increasing use with few side effects. Animal-assisted intervention (AAI), also called pet therapy, acts as a psychosocial and adjunctive treatment for symptom control (Levinson, 1965).…”
Section: Introductionmentioning
confidence: 99%
“…12,13 Whereas integrative medicine and care are slowly finding their way into the German hospital landscape, 3 university hospitals still have an ambivalent attitude toward T&CM. 14,15 There is growing research on supportive T&CM interventions for specific symptoms in pediatric oncology such as fatigue, psychological stress, and pain, [16][17][18] and also few descriptions of implementation projects in pediatric settings. 19,20 To date, however, limited research on the implementation, applicability, and evaluation of integrative care in the highly specialized field of children's oncology is available in Germany.…”
Section: Introductionmentioning
confidence: 99%
“…Two of the studies related to hypnosis were included in the meta-analysis and the overall effect on nausea and pain was insignificant. However, previous research [ 57 ] reported that hypnotherapy significantly reduced cancer-related procedural pain combined with standard care ( p < 0.00001). Despite insignificant effect, it should be noted that the current meta-analysis was conducted with only two studies.…”
Section: Discussionmentioning
confidence: 92%